Pathogenesis of developmental anomalies of the central nervous system induced by congenital cytomegalovirus infection. Issue 2 (10th January 2017) - Kawasaki, Hideya; Kosugi, Isao; Meguro, Shiori; Iwashita, Toshihide
Abstract : In humans, the herpes virus family member cytomegalovirus (CMV) is the most prevalent mediator of intrauterine infection‐induced congenital defect. Central nervous system (CNS) dysfunction is a distinguishing symptom of CMV infection, and characterized by ventriculoencephalitis and microglial nodular encephalitis. Reports on the initial distribution of CMV particles and its receptors on the blood brain barrier (BBB) are rare. Nevertheless, several factors are suggested to affect CMV etiology. Viral particle size is the primary factor in determining the pattern of CNS infections, followed by the expression of integrin β1 in endothelial cells, pericytes, meninges, choroid plexus, and neural stem progenitor cells (NSPCs), which are the primary targets of CMV infection. After initial infection, CMV disrupts BBB structural integrity to facilitate the spread of viral particles into parenchyma. Then, the initial meningitis and vasculitis eventually reaches NSPC‐dense areas such as ventricular zone and subventricular zone, where viral infection inhibits NSPC proliferation and differentiation and results in neuronal cell loss. These cellular events clinically manifest as brain malformations such as a microcephaly. The purpose of this review is to clearly delineate the pathophysiological basis of congenital CNS anomalies caused by CMV.